Between reappropriations and legacies. The political lexicon of human rights in the Argentine rights of the 21st century (Clepsidra - Interdisciplinary Journal of Memory Studies, 2022)
In the last few years, the Argentine rights have recovered the language of human rights to define their position on the public scene and articulate their criticisms of political projects with a national and popular trajectory. Considering the novel and unprecedented nature of this operation, this article investigates the processes of resignification that it entails, paying particular attention to two aspects that are usually largely overlooked in studies on the subject. On the one hand, the destabilization and dispossession carried out by the Cambiemos government of the senses rooted in the struggle carried out by human rights organizations and the unprecedented discursive opening scenario that it configures. On the other hand, the proliferation of political uses that liberal and conservative sectors promote in their dispute to fix the meaning of human rights to regressive discourses in terms of expanding citizenship.
Keywords: Human Rights, Argentine Rights, Resignification, Political Discourse